Pengaruh Konsentrasi Sorbitol terhadap Warna, Transmisi Cahaya, dan Transparansi Film Edible Film dari Gelatin Usus Ayam - Damayanti, Nofita; Wulandari, Eka; Gumilar, Jajang (Unpad Press, 2023)
Edible film have known as an innovative eco-friendly packaging materials because can reduce plastic wastes. One of primary components to form edible film are gelatine which hydrocolloids and contain gel-forming agents. This study used gelatine from intestines of chicken with sorbitol as plasticizer to increase film plasticity properties. Edible film are applied to surface a food should have to good quality and visual appearance. Therefore, this study aims to determine the effect of sorbitol on colour, light transmission, and transparency edible film of gelatine from chicken intestines. The method of this study carried out by experimental using a completely randomized design (CRD) anova and duncan’s test with 5 concentration treatments are, 10%, 20%, 30%, 40%, and 50%, each treatment have 4 times repetition. Statistical analysis result obtained that sorbitol concentration treatments significantly effected (P<0.05) the variables have tested. The best edible film are film contains 30% concentration of sorbitol with colour value L* 26.32, a* 33.32, and b* 0.36 (light, redness, and yelowish), light transmission value are 0.43—27.39 (200—800 nm), and transparency value 4.09.